'Dear Doctor': a randomised controlled trial of a text message intervention to reduce burnout in trainee anaesthetists. (13th January 2022) - Brazier, A.; Larson, E.; Xu, Y.; Judah, G.; Egan, M.; Burd, H.; Darzi, A.
Summary: One in four doctors in training in the UK reports feeling 'burnt out' due to their work and similar figures are reported in other countries. This two‐group non‐blinded randomised controlled trial aimed to determine if a novel text message intervention could reduce burnout and increase well‐being in UK trainee anaesthetists. A total of 279 trainee anaesthetists (Core Training Year 2, Specialty Training Years 3 or 4) were included. All participants received one initial message sharing support resources. The intervention group (139 trainees) received 22 fortnightly text messages over approximately 10 months. Messages drew on 11 evidence‐based themes including: gratitude; social support; self‐efficacy; and self‐compassion. Primary outcomes were burnout (Copenhagen Burnout Inventory) and well‐being (Short Warwick‐Edinburgh Mental Well‐being Scale). Secondary outcomes were as follows: meaning in work; professional value; sickness absence; and consideration of career break. Outcomes were measured via online surveys. Measures of factors that may have affected well‐being were included post‐hoc, including the impact of COVID‐19 (the first UK wave of which coincided with the second half of the trial). The final survey was completed by 153 trainees (74 in the intervention and 79 in the control groups). There were no significant group differences in: burnout (β = ‐1.82, 95%CI ‐6.54–2.91, p = 0.45); well‐being (‐0.52, ‐1.73–0.69, p = 0.40); meaning (‐0.09, ‐0.67–0.50, p = 0.77); value (‐0.01, ‐0.67–0.66, p = 0.99); sick days (0.88, ‐2.08–3.83, p = 0.56); or consideration of career break (OR = 0.44, ‐0.30–1.18, p = 0.24). Exploratory post‐hoc analysis found the intervention was associated with reduced burnout in participants reporting personal or work‐related difficulties during the trial period (‐9.56, ‐17.35 to ‐1.77, p = 0.02) and in participants reporting that the COVID‐19 pandemic had a big negative impact on their well‐being (‐10.38, ‐20.57 to ‐0.19, p = 0.05). Overall, this trial found the intervention had no impact. However, given this intervention is low cost and requires minimal time commitment from recipients, it may warrant adaptation and further evaluation.